2020
DOI: 10.3390/ani10061049
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic and Genotypic Characterization of Virulence Factors and Susceptibility to Antibiotics in Salmonella Infantis Strains Isolated from Chicken Meat: First Findings in Chile

Abstract: Salmonella Infantis is a zoonotic pathogen that causes gastroenteritis in humans and animals, with poultry being its main reservoir. In Chile, there are no data to characterize S. Infantis strains in poultry production. In this study, 87 S. Infantis strains were isolated from chicken meat for sale in supermarkets in Santiago, Chile, and characterized according to their virulence genes, biofilm formation abilities, antibiotic susceptibility, and resistance genes. Through polymerase chain reaction or PCR, the st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

7
30
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(42 citation statements)
references
References 57 publications
7
30
1
Order By: Relevance
“…The presence of Salmonella strains was mainly observed in serogroups B and C1 within different animal populations in Chile. Coincident with our study, other studies carried out in Chile have found these common serovars to be Enteritidis, Typhimurium and Infantis (serogroup D, B and C1) [ 15 , 18 , 22 , 24 , 27 , 28 , 29 , 30 ]. However, S. Enteritidis has represented the highest percentage of isolates [ 15 , 16 , 17 , 18 , 19 , 22 ].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The presence of Salmonella strains was mainly observed in serogroups B and C1 within different animal populations in Chile. Coincident with our study, other studies carried out in Chile have found these common serovars to be Enteritidis, Typhimurium and Infantis (serogroup D, B and C1) [ 15 , 18 , 22 , 24 , 27 , 28 , 29 , 30 ]. However, S. Enteritidis has represented the highest percentage of isolates [ 15 , 16 , 17 , 18 , 19 , 22 ].…”
Section: Discussionsupporting
confidence: 90%
“…[ 29 ]. Similarly to this report, a previous article [ 30 ] also indicated a high contamination by S. Infantis of chicken meat available for consumption in supermarkets. However, a low prevalence is reported in backyard poultry farms (approximately 1%) [ 15 ].…”
Section: Discussionsupporting
confidence: 81%
“…Lower resistance to tetracycline and chloramphenicol occurred in this study. In Chile, Salmonella infantis from chicken meat was resistant to amoxycillin/clavulanic acid (3.5%), azithromycin (2.3%), ceftriaxone (67.8%), chloramphenicol (64.4%), ciprofloxacin (2.3%), gentamycin (11.5%), tetracycline (95.4%), and sulfamethoxazole/trimethoprim (49.4%) [ 44 ]. This study found higher resistance to amoxycillin/clavulanic acid, azithromycin, and gentamycin, but lower for the rest of the antibiotics tested.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, a recent publication from Chile reported that 24% of broiler meat samples ( n = 361) were positive to the isolation of S . Infantis ( 61 ). This data highlights the necessity of more research in the field to better understand the epidemiology of Salmonella in the region.…”
Section: Discussionmentioning
confidence: 99%